Aspek Sosiologis dalam Novel di Bawah Langit yang Sama Karya Helga Rif - Astuti, Putri Mayang; Jumadiah, Sri (Humanis; Vol 24 No 3 (2020), 2020)
This study aims to describe (1) the structure that builds the novel Di Bawah langit yang Samaby Helga Rif; and (2) the sociological aspects contained in the novel Di Bawah Langit yang Sama by Helga Rif. The theory used in this research is Stanton's structural theory and literary sociology Ian Watt. Data collection methods used are library methods as well as reading and note-taking techniques. Data analysis was performed using descriptive analytic methods. Data analysis techniques using reading, interpretive, and note taking techniques. The results of this study indicate that the intrinsic elements analyzed in the novel under the same sky include: characterizations, plots, and settings. The sociological aspects analyzed in the novel Di Bawah Langit yang Sama are social aspects, moral aspects, education aspects, economic aspects, and love aspects. Social aspects are shown in the lives of Balinese people. Moral aspects found are good morals. The educational aspects analyzed include formal and informal education. Economic aspects are analyzed using social stratification, namely upper class and middle class society. Aspects of romance discuss the love of different religions between Indira and Maximilian.